PENGELOLAAN SUMBER DAYA MANUSIA LABORATORIUM KLINIK - Noormartany Noormartany (Indonesian Association of Clinical Pathologist and Medical laboratory, 2011)
Clinical laboratories should have higher competitiveness and healthiness to be survived in the globalization era. The very basic assets are vision, mission, and objectives which are agreed upon them. To establish these objectives are required the availability of the human resources which can perform professionally. They can serve efficiently and effectively due to their increasing professionalism. This happened by a continuing enhanced development of the human resources. The only way to achieve this objective is by effecting the Total Quality Management which emphasizes the personal development through an objective appraisal system